Penghulu's Assistance in Providing Premarital Guidance to Realize a Sakinah Mawaddah Warahmah (Samara) Family at KUA Tanjung Morawa - Risma, Ade; Ritonga, Elfi Yanti (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
This assistance aims to analyze Penghulu's Islamic Communication Assistance Strategy in Providing Premarital Guidance to Create a Sakinah Mawaddah Warahmah (Samara) Family in Kua Tanjung Morawa. The approach uses PAR (Participatory Action Research). The Islamic communication assistance strategy implemented by the headmen at KUA Tanjung Morawa in providing pre-marital guidance plays a very important role in creating a Sakinah Mawaddah Warahmah (SAMARA) family. The approach used includes a deep understanding of Islamic values, effective communication techniques, as well as empathy and emotional support for prospective bride and groom couples. Through structured guidance and based on Islamic principles, the bride and groom are able to help prospective bride and groom couples understand the importance of commitment, mutual understanding and cooperation in building a harmonious family, so that the goal of achieving a sakinah, mawaddah and warahmah family can be realized more fully real.